DNA analysis of ancient dogs of the Americas: Identifying possible founding haplotypes and reconstructing population histories. Issue 79 (February 2015) - Witt, Kelsey E.; Judd, Kathleen; Kitchen, Andrew; Grier, Colin; Kohler, Timothy A.; Ortman, Scott G.; Kemp, Brian M.; Malhi, Ripan S.
Abstract: As dogs have traveled with humans to every continent, they can potentially serve as an excellent proxy when studying human migration history. Past genetic studies into the origins of Native American dogs have used portions of the hypervariable region (HVR) of mitochondrial DNA (mtDNA) to indicate that prior to European contact the dogs of Native Americans originated in Eurasia. In this study, we summarize past DNA studies of both humans and dogs to discuss their population histories in the Americas. We then sequenced a portion of the mtDNA HVR of 42 pre-Columbian dogs from three sites located in Illinois, coastal British Columbia, and Colorado, and identify four novel dog mtDNA haplotypes. Next, we analyzed a dataset comprised of all available ancient dog sequences from the Americas to infer the pre-Columbian population history of dogs in the Americas. Interestingly, we found low levels of genetic diversity for some populations consistent with the possibility of deliberate breeding practices. Furthermore, we identified multiple putative founding haplotypes in addition to dog haplotypes that closely resemble those of wolves, suggesting admixture with North American wolves or perhaps a second domestication of canids in the Americas. Notably, initial effective population size estimates suggest at least 1000 female dogs likely existed in the Americas at the time of the first known canid burial, and that population size increased gradually over time before stabilizing roughly 1200 years before present.